Efeito do resveratrol na qualidade e desenvolvimento de embriões bovinos criopreservados ou conservados em meio holding - Silva, Ariany Rafaella Neto (2015)
This study was developed with the objective of evaluating the response of bovine embryos produced in vitro (PIV) the addition of resveratrol (Resv) to recultivo to embryos vitrified (Experiment 1-E1) and medium Holding for fresh embryos (Experiment 2-E2) to check the maintenance or improvement in the quality of these embryos. In E1 PIV vitrified bovine embryos were heated and recultivados in the medium containing 0.5 μM of resveratrol, evaluating the re-expansion rates, hatching and cell quality by analysis of TUNEL. In E1, the hatching rate of recultivo more than 24 hours after (P < 0.05) in the Resv Group (37,7 vs. 19,1%). The rate of embryos according to the stage of development did not show difference between treatments. Even in E1, for fresh embryos PIV the total number of cells (NTC) was superior to that found in the vitrified embryos (131,6 vs 88,8 and 82,7%) , as well as the NCA (number of apoptotic cells) was lower (6,3 ± 0,8) compared with control groups and resveratrol (15,8 ± 1.2 and 13,5 ± 1,0), which did not differ among themselves in these variables. No difference was observed in embryos degenerates and reactive oxygen species (ROS) and Glutathione (GSH). In E2 bovine embryos were fresh bottled PIV in 0,25 ml straws with a holding in the presence (TR6 and TR10) or absence (TH6 and TH10) of resveratrol and kept on warming plate to 36° C in different times, six and 10 hours, followed by the unloading spouts and recultivo until 24 hours. Hatching rates at 24 hours of embryos treated with antioxidant tended to be greater than in the control. Bx TR10 rates was higher (51,2%) the TR6 (30,8%) (P < 0.05), the other stages of development were similar, the NTC was lower in TH10. The index of EROS was superior in TH10 (23,4126 ± 1,5661). The values of the GSH TR6 (95,2208) were larger than TH6 (30,7594) (P < 0.05), the TR10 issuing GSH (49,5330 ± 6,5332) did not differ from TH10 group (47,2044) (P > 0,05).